RODRIGO JIMÉNEZ DE RADA Y LA COMPILACIÓN HISTORIOGRÁFICA DEL CÓDICE DE BAMBERG HIST. 3. (2019) - DE CARLOS VILLAMARÍN, HELENA
Abstract : Rodrigo Jimenez de Rada's Historia Romanorum depends, when describing some of Aeneas's adventures and the origins of Rome, both on the anonymous paraphrase of the Excidium Troie called Excidium, and on the paraphrase of Paul the Deacon's Historia Romana copied in some manuscripts related to the codex Bamberg, Staatsbibliothek Hist. 3. Some features of Jimenez de Rada's Historia de rebus Hispanie also follow the paraphrase of Exordia Scythica copied in the same family of manuscripts. The antigraphus of the Bamberg codex, probably written in Campania in the tenth century, seems to have been the textual model for Jimenez de Rada, a man who used to travel to Italy and visit the papal court. Besides proving this fact, this paper aims to follow the steps of Excidium Troie, a text whose presence in medieval Spain is detectable, although in a particular version, in some manuscripts of the late 13th century.